Pengaruh Nilai Informasi dan Sosial pada Co-Consumption dan Co-Production antar Anggota Kaskus: Perspektif Modal Sosial - Sukoco, Badri Munir; Aditya, Mohamad Lambang (Jurnal Manajemen Teknologi, 2011)
Consumers co-create values through co-consumption (with other consumers) and co-production (with producers). This study argues that members' perceptions on informational and social values contribute to co-creation, which is stronger when they have greater product involvement. Further arguments indicate that members' perceptions on informational and social values are determined by social capital inside the community. The developed hypotheses are tested on 204 Kaskus community members who are affiliated with 6 different brands on two product categories, mobile phone and snack. The results indicate that social capital positively influences members' perception on informational and social values. Social value influence co-consumption and co-production, while informational value mainly influence co-production. The moderating effect of product involvement exists on the influence of social value on co-production.Keywords: co-consumption, co-production, social capital, informational value, social value, productinvolvement, virtual community